2003
DOI: 10.1086/367609
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Jets in Collapsars

Abstract: We examine the propagation of 2-dimensional relativistic jets through the stellar progenitor in the collapsar model for gamma-ray bursts. In agreement with previous studies, we find that relativistic jets are collimated by their passage through the stellar mantle. Interaction of these jets with the star and their own cocoons also causes mixing that sporadically decelerates the flow. We speculate that this mixing instability is chiefly responsible for the variable Lorentz factor needed in the internal shock mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
463
4
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 453 publications
(519 citation statements)
references
References 40 publications
46
463
4
6
Order By: Relevance
“…The early phase of the propagation of jets in collapsars has been studied by nonrelativistic (MacFadyen & Woosley 1999;MacFadyen et al 2001) as well as special (Zhang & MacFadyen 2003) or general relativistic (Aloy et al 2000;Aloy & Martí 2002) hydrodynamic simulations in two dimensions (i.e., assuming axial symmetry). Also first axisymmetric magnetohydrodynamic simulations have been done for the formation of polar outflows from the central non-rotating BH in a collapsar in both Newtonian (Proga et al 2003; using a pseudoNewtonian potential, Pacyński & Wiita 1980) and general relativity (Mizuno et al 2004; assuming a fixed Schwarzshild metric).…”
Section: Introductionmentioning
confidence: 99%
“…The early phase of the propagation of jets in collapsars has been studied by nonrelativistic (MacFadyen & Woosley 1999;MacFadyen et al 2001) as well as special (Zhang & MacFadyen 2003) or general relativistic (Aloy et al 2000;Aloy & Martí 2002) hydrodynamic simulations in two dimensions (i.e., assuming axial symmetry). Also first axisymmetric magnetohydrodynamic simulations have been done for the formation of polar outflows from the central non-rotating BH in a collapsar in both Newtonian (Proga et al 2003; using a pseudoNewtonian potential, Pacyński & Wiita 1980) and general relativity (Mizuno et al 2004; assuming a fixed Schwarzshild metric).…”
Section: Introductionmentioning
confidence: 99%
“…LloydRonning et al (2004) showed that allowing the parameters of the jet profile to vary somewhat from burst to burst-the jet profile is now only quasi-universal-results both in variations in the value of E and deviations from a pure power law. While numerical modeling of hypernovae (Zhang et al 2003) shows that the surface energy density of the outflows should vary with off-axis angle, it does not predict the profile; thus, the profiles are fitted empirically to the data. Consequently, the observed E iso probability distribution is not a powerful discriminant between the two jet structure models.…”
Section: Introductionmentioning
confidence: 99%
“…A typical duration of a long GRB is a few tens of seconds, and in that time several solar masses are accreted by the black hole (Zhang et al 2003). Then, we adopṫ M = 0.1 M s −1 and q j = 0.02.…”
Section: Basic Modelmentioning
confidence: 91%